Study of the reactor temperature effect on H2 production from steam decomposition using DBD plasma - Mostafa El-Shafie; Shinji Kambara; Yukio Hayakawa (Energy Reports, 2020)
Heat transfer data for the effect of the reactor and surrounding temperature on the hydrogen production from water vapour decomposition using Dielectric-Barrier Discharge (DBD) plasma are reported. The water vapour was injected into the plate micro channel reactor (PMCR) where the PMCR and its surrounding temperatures were raised using an insulated constant temperature heater type in a range of 20-130°C. This experiment was run at the following steam inlet conditions: pressure 100~kPa, temperature 300°C and flow rates of 100-200~ml/h, while the plasma applied voltage was in a range of 14-18 kV. In particular, the concentrations of hydrogen and oxygen species were analysed using gas phase chromatography (GC). It was observed that the hydrogen concentration percent increased with the reactor and surrounding temperature increased at all tested steam flow rates. Also, it was seen that the maximum obtained H2 concentrations were at high reactor temperature 130°C and plasma applied voltage of 18 kV. The effect of reactor temperature on the total heat transfer resistances at different steam flow rates was investigated. The trend behaviour of these resistances reveals interesting information about how these resistances interact and distribute according to the reactor heating temperature. Also, it was found that the total heat transfer rate decreased with the reactor temperature increased while the overall heat transfer rate increased with plasma voltage and reactor heating temperature. It can be concluded that the DBD plasma effect improved by decreasing the temperature difference between input steam and the PMCR temperatures. Further, it was clear that the steam dissociation processes not mainly depending on the plasma applied voltage but also the reactor heating temperature.
Keywords: 330; DBD plasma; Hydrogen production; Steam decomposition